Cubic garnet solid polymer electrolyte for room temperature operable all-solid-state-battery - Luu, Van Tung; Nguyen, Quoc Hung; Park, Moon Gyu; Nguyen, Hoang Long; Seo, Min-Ho; Jeong, Soon-Ki; Cho, Namchul; Lee, Young-Woo; Cho, Younghyun; Lim, Sung Nam; Jun, Yun-Seok; Ahn, Wook (Journal of materials research and technology, 2021)
Solid polymer electrolytes are promising candidates for implementation in next-generation all-solid-state batteries (ASSBs) which could replace conventional batteries used today. However, the materialization of ASSBs on a mass scale is restricted by the low ionic conductivity and high interfacial resistance of solid electrolytes. In this work, succinonitrile (SN) with lithium (trifluoromethylsulphonyl)imide (LiTFSI) and Al-doped Li7La3Zr2O12 (Al-LLZO) nanoparticles were used to improve the ionic conductivity of a polyethylene oxide-based composite electrolyte. The Al-LLZO nanoparticles were synthesized by a facile synthesis process at low temperatures, which contributed to an enhancement in the ionic conductivity. A solid polymer electrolyte with 7.5 wt% of Al-LLZO and 15 wt% of SN achieved a high ionic conductivity of 4.17 × 10−4 Scm−1 at room temperature and a large value of 0.451 for the lithium-ion transport number at 60 °C. By adding 10 wt% SN and 10 wt% of Al-LLZO in the LiFePO4 cathode, the cell could operate at 25 °C with a specific capacity of 130 mAh g−1 and 89% capacity retention after 200 cycles at current density of 20 mA g−1. This study therefore proposes a solution to improve the ionic conductivity of solid polymer electrolytes in all-solid-state batteries.